2006
DOI: 10.1029/2006gl026771
|View full text |Cite
|
Sign up to set email alerts
|

Krakatoa lives: The effect of volcanic eruptions on ocean heat content and thermal expansion

Abstract: [1] A suite of climate model experiments indicates that 20th Century increases in ocean heat content and sea-level (via thermal expansion) were substantially reduced by the 1883 eruption of Krakatoa. The volcanically-induced cooling of the ocean surface is subducted into deeper ocean layers, where it persists for decades. Temporary reductions in ocean heat content associated with the comparable eruptions of El Chichón (1982) and Pinatubo (1991) were much shorter lived because they occurred relative to a non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
81
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 21 publications
15
81
0
2
Order By: Relevance
“…Previous studies have suggested that the oceans were affected by Krakatau's cooling for some decades (e.g. Gleckler et al, 2006). If the cooling associated with Krakatau is indeed less than the models suggest because of the mechanism explained above, model predictions of 20th century heat content and sea level change may be biased.…”
Section: Discussion and Implications For Krakataumentioning
confidence: 85%
“…Previous studies have suggested that the oceans were affected by Krakatau's cooling for some decades (e.g. Gleckler et al, 2006). If the cooling associated with Krakatau is indeed less than the models suggest because of the mechanism explained above, model predictions of 20th century heat content and sea level change may be biased.…”
Section: Discussion and Implications For Krakataumentioning
confidence: 85%
“…In terms of surface cooling pattern, Jones et al (2005) obtained the largest cooling over north-eastern America and European Arctic and eastern Siberia, whereas in our model the biggest response appears over central Siberia. This difference seems to be due to the missing feedback related to atmospheric By analysing a series of ocean-atmosphere GCM experiments recently performed by the climate modelling community, Gleckler et al (2006) investigated the effect of volcanic eruptions on oceanic heat content and penetration of ocean cooling with time. In response to the series of volcanic eruptions that occurred before industrialization, ocean heat content decreased substantially and the low heat content persisted for a long time as a result of recurring volcanic eruptions.…”
Section: Comparison To Other Model Resultsmentioning
confidence: 99%
“…There have been many studies on the effect of volcanic eruptions on global climate change (Robock 2000;Stenchikov et al 1998Stenchikov et al , 2002Stenchikov et al , 2004Stenchikov et al , 2009Kirchner et al 1999;Yang and Schlesinger 2002;Shindell et al 2004;Gleckler et al 2006;Frölicher et al 2011;Mignot et al 2011;Ottera et al 2010;Zanchettin et al 2012). The studies showed that large volcanic eruptions emit sulphur gases into the stratosphere, which become sulphate aerosols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). This GMTSL fall is caused by decreased ocean temperatures as a result of negative radiative forcing after volcanic eruptions and is followed by a slow recovery (Church et al 2005;Gleckler et al 2006;Gregory et al 2006). The net GMTSL change in historical simulations with volcanic forcing is dependent on whether or not volcanic forcing was included in the control run, as the omission of volcanic forcing in the control run results in a negative bias in GMTSL when volcanic forcing is introduced in the historical period (Gregory 2010;Gregory et al 2013).…”
Section: Global Mean Thermosteric Sea Level Changementioning
confidence: 99%